2020
DOI: 10.1071/an19218
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol alleviates heat stress-induced impairment of intestinal morphology, barrier integrity and inflammation in yellow-feather broilers

Abstract: Context Heat stress is one of the problems commonly found in broiler industry in tropic and subtropic regions that results in impairment of intestinal integrity, leading to inflammation and poor performance. Aims This study aimed to investigate the effect of dietary resveratrol supplementation on growth performance, intestinal morphology and barrier integrity, and inflammation response of yellow-feather broilers under heat stress. Methods In total, 288 birds (28-day-old) were randomly allotted to three treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
2
18
1
1
Order By: Relevance
“…In this study, based on the analysis of selected physical gut barrier function-related molecular expression, four-week HS exposure decreased the tight junction protein expression of the duodenum, including occludin and ZO-1, and their absence could be responsible for an increase in intestinal permeability. Similar findings were also obtained by Liu et al [ 9 ] and He et al [ 35 ]. Meanwhile, the present study evaluated the mitigation effects of dietary ADP supplementation on duodenal barrier function-related molecular expression of broilers under HS.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, based on the analysis of selected physical gut barrier function-related molecular expression, four-week HS exposure decreased the tight junction protein expression of the duodenum, including occludin and ZO-1, and their absence could be responsible for an increase in intestinal permeability. Similar findings were also obtained by Liu et al [ 9 ] and He et al [ 35 ]. Meanwhile, the present study evaluated the mitigation effects of dietary ADP supplementation on duodenal barrier function-related molecular expression of broilers under HS.…”
Section: Discussionsupporting
confidence: 91%
“…Consistently, Liu et al [ 6 ] found that 5 weeks of HS decreased the duodenal villus height of yellow-feathered broilers. He et al [ 35 ] suggested that 14 d of HS exposure induced a reduction in jejunal villus height of yellow-feathered broilers. Zhang et al [ 14 ] reported that the Cobb broilers subjected to 21 d of HS resulted in a lower villus height and ratio of villus height to crypt depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat stress may induce reactive oxygen species (ROS) production, cause antioxidant system disorders, and cause damage to the immune organs in vivo [32]. In a recent report, our research group observed that dietary resveratrol supplementation in broilers was successful in partially alleviating the detrimental effects of heat stress on the function of the intestinal barrier, by restoring the damaged villus-crypt structure, altering the mRNA expression of intestinal heat-shock proteins, secreted immunoglobulin A, and close junctionrelated genes and inhibiting pro-inflammation secretion [33]. Zhang et al [34] reported that dietary supplementation with resveratrol in broilers could partly reverse the adverse effects of heat stress on the growth of immune organ by reestablishing redox status and inhibiting apoptosis.…”
Section: The Anti-inflammatory Activity Of Resveratrolmentioning
confidence: 99%
“…Our previous study has reported that RSV supplementation in heat stress-induced black-boned chickens improved growth performance and reduced oxidative stress by modulating the expression of heat shock genes in immune organs ( 12 ). RSV also alleviated heat-stressed impairment of the intestine by improving the barrier function ( 13 ).…”
Section: Introductionmentioning
confidence: 99%